2016
DOI: 10.1057/eps.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

an audit of transferable skills teaching in uk politics departments

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported License Newcastle University ePrints -eprint.ncl.ac.uk Clark A, Martin T. An Audit of Transferable Skills Teaching in UK Politics Departments. European Political Science 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…A paper exploring skills and foreign policy courses in Germany identified that despite acknowledging the skills issues, 'alternative innovative teaching methods, such as the drafting of policy papers, seem only rarely to have found their way into curricula' (Nieman and Heister 2010). Research has shown that the politics/IR curricula in the UK provides students with a range of transferable skills that they will find of great use as they move towards employment, the discipline is poor in highlighting this: 'if we don't tell students what we are teaching them, then they won't realise that they have gained a whole range of skills through their study of politics' (see Clark and Martin 2016). An obvious way to ensure all students engage with the skill development aspect of this agenda is to embed and assess the skills via the choice of assessment (Curtis 2013) and across the curricula (Adriaensen et al 2019).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper exploring skills and foreign policy courses in Germany identified that despite acknowledging the skills issues, 'alternative innovative teaching methods, such as the drafting of policy papers, seem only rarely to have found their way into curricula' (Nieman and Heister 2010). Research has shown that the politics/IR curricula in the UK provides students with a range of transferable skills that they will find of great use as they move towards employment, the discipline is poor in highlighting this: 'if we don't tell students what we are teaching them, then they won't realise that they have gained a whole range of skills through their study of politics' (see Clark and Martin 2016). An obvious way to ensure all students engage with the skill development aspect of this agenda is to embed and assess the skills via the choice of assessment (Curtis 2013) and across the curricula (Adriaensen et al 2019).…”
Section: Contextmentioning
confidence: 99%
“…In 2009 Boys and Keating argued that 'international relations and political science curricula in the UK would benefit from the wider use of this tool [policy briefs]' and yet more recent research suggests policy briefings are still an 'underutilized pedagogical tool' (Chagas-Bastos and Burges 2018). In the UK, it was found that policy brief writing was evident in only 2.3% of Russell Group modules and 1.4% of Non-Russell Group modules 27 (Clark and Martin 2016). Chagas-Bastos and Burges (2018) suggest the syllabi sampled in the US, Canada, Australia, Brazil, and Colombia show similar usage rates.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the debate about skills acquisition concerns the concept of 'employability' and its implications. Clark and Martin (2016), for example, argue that particularly in the UK the employability agenda has been driven by government policies, national student surveys, concerns of parents and students faced with high tuition fees, and the Bologna process (see also Lee et al 2016). As Sin and Neave (2016) show, European policy-makers and employers have promoted a discourse that stresses students' need to become 'employable' individuals, and emphasises the responsibility of HE institutions to equip students with the necessary skills to do so (see also Crebert et al 2004, on Australia; Mohan et al 2010, on the United States).…”
Section: Skills and Mapping Their Progressionmentioning
confidence: 99%
“…Arguably, such a comprehensive approach to teaching generic skills is especially important in the social sciences, where students are usually not trained in a particular profession (Clark and Martin 2016), and where 'critical engagement with […] the social world' is central to curricula (Lee et al 2016: 108). Maurer and Mawdsley (2014: 39) find that programmes about policies and politics are also 'well-suited' for a comprehensive approach to the teaching of skills, as 'engagement with the policy environment is already embedded in mainstream understandings of how to teach the subject'.…”
Section: Skills and Mapping Their Progressionmentioning
confidence: 99%
See 1 more Smart Citation